Rethinking Intelligence: From Human Cognition to Artificial Futures - Habib Hamam (Universitas Negeri Surabaya or The State University of Surabaya, 2025)
The rapid advancement of AI technologies raises pressing questions about the nature and future direction of intelligence. A key challenge is to understand how human and artificial intelligences differ, not just in form but in function, and how they should be evaluated in a shared context. This paper proposes a structured framework based on 15 measurable conditions of intelligence, such as memory, adaptability, specialization, and ethical alignment. Our main contribution lies in connecting these conditions to nine key directions of AI development—such as responsible AI, human–machine collaboration, and quantum AI—to outline how intelligence can be evaluated and guided across both natural and synthetic domains. Methodologically, we cross-analyze these dimensions using a 15×9 matrix, providing both a diagnostic tool and a conceptual roadmap for future AI development. This approach blends insights from cognitive science, applied AI, ethics, and philosophy. Our findings show that intelligence must be judged not just by computational capability but by interpretability, ethical grounding, and social utility. Contextual and hybrid systems—those that adapt to environments and align with human values—emerge as the most promising. We conclude by calling for an interdisciplinary approach to build intelligence systems that are not only powerful but also trustworthy and socially meaningful.